2021
DOI: 10.1029/2021je006845
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of Apollo 17 Soil Sample 78421 by Solar Wind Protons

Abstract: Solar wind induced hydroxylation on the Moon and other airless bodies is critically important to understand how space weathering produces and distributes potential hydrogen-bearing resources such as water. Our understanding of these hydrogen-bearing resources was significantly advanced in 2009 and 2010 when hydroxyls in the mid-latitude and cool terminator regolith was observed via infrared spectroscopy (Clark, 2009;Pieters et al., 2009;Sunshine et al., 2009), and when water-ice within permanently shadowed pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
(86 reference statements)
1
18
0
Order By: Relevance
“…The desorption rate of adsorbed H 2 O as described in Poston et al (2015) is likely the controlling factor for the change in band minima. However, McLain et al (2021) found that the 3 μm band of the Apollo sample 78,421 was shifted to longer wavelengths with increased proton irradiation fluence. The spectra from that work lack the 6.1 μm water feature.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The desorption rate of adsorbed H 2 O as described in Poston et al (2015) is likely the controlling factor for the change in band minima. However, McLain et al (2021) found that the 3 μm band of the Apollo sample 78,421 was shifted to longer wavelengths with increased proton irradiation fluence. The spectra from that work lack the 6.1 μm water feature.…”
Section: Discussionmentioning
confidence: 93%
“…However, McLain et al. (2021) found that the 3 μm band of the Apollo sample 78,421 was shifted to longer wavelengths with increased proton irradiation fluence. The spectra from that work lack the 6.1 μm water feature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that ~20–50% of solar wind protons can be bonded with oxygen to form OH/H 2 O 49 . Based on this, we calculated the surface density of hydrogen ( ρ H ) from the following equation 50 : where the p is the fraction of hydrogen bonded to oxygen, and the value of 20–50% was taken for our calculations. D is the penetration depth for solar wind protons, N A is the Avogadro’s constant (6.02 × 10 23 ), and ρ m is the density of minerals, which is 3.35 g/cm 3 for olivine, 2.73 g/cm 3 for plagioclase, and 3.21 g/cm 3 for pyroxene.…”
Section: Methodsmentioning
confidence: 99%
“…Combined with the proton flux of solar wind (4 × 10 15 H/cm −2 /yr), we calculated the accumulated implantation time of solar wind for lunar minerals to be ~270–4212 years (Supplementary Table 5 ). However, there may be considerable uncertainty in these values, such as the conversion of proton flux to OH/H 2 O, for which values can vary considerably 15 , 50 , the complex factors influencing the formation processes of solar wind-derived water, the escape process of solar wind-derived water by temperature and ultraviolet radiation, the diffusion of solar wind-derived water. Estimation of the exposure age of solar wind implantation for lunar soil still requires further investigation.…”
Section: Methodsmentioning
confidence: 99%
“…The Supplementary Material contains spectral comparisons and accompanying discussion of the hydrated MORB glasses used here to the 3 μm band shape from lunar remote sensing data from the InfraRed Telescope Facility (IRTF, Figure S1 in Supporting Information S1) and from M 3 (Figure S2 in Supporting Information S1). The shape of the MORB 3 μm band can also be compared to the hydroxyl feature in laboratory spectra of proton-irradiated Apollo soils (Ichimura et al, 2012;McLain et al, 2021). Ubiquitous (but unquantified) adsorbed surface water is present in the laboratory reference spectra of Apollo samples we used (Figure S3 in Supporting Information S1) due to the high reactivity of lunar soil samples, with similar band shape to the hydrated MORB glasses.…”
Section: Spectral Data Setsmentioning
confidence: 99%